Praxis as a Perspective on International Politics - Hellmann, Gunther (Book collections on Project MUSE., 2022)
Bringing together leading figures in the study of international relations, this collection explores praxis as a perspective on international politics and law. It builds on the transdisciplinary work of Friedrich Kratochwil to reveal the scope, limits and blind spots of praxis theorizing.